Application of pre-emulsion technology in skinless smoked sausages - Del Rosario, Marilag De Chavez; Mateo, Liwayway T. (1992.)
Two aspects of the application of pre-emulsion in skinless smoked sausages were considered for this study. One is the determination of the most suitable emulsifier in the pre-emulsion and the other is the establishment of the level of incorporation of pre-emulsion in sausages. Results of water-holding capacity tests (WHC) of the three nonmeat proteins showed that ISP had the greatest capacity to hold and bind water. Sensory evaluation results revealed similarity between sausages without pre-emulsion and those with ISP as emulsifier. Both received the highest rating in terms of general acceptability. The latter was also found to be the most inexpensive among the four pre-emulsion. Thus, it was established that ISP was the best emulsifier to use for the skinless smoked sausages among the three nonmeat proteins and was applied in the second phase of the study. Phase 2 involved the establishment of the best level of pre-emulsion incorporation in the sausages. 10%, 15%, 20% were the levels considered. The panelists in the sensory evaluation rated 15% as the most preferred in terms of taste. 10% was determined to be statistically similar to 15% although the cost of the sausage was higher at this level. 20% pre-emulsion incorporation proved to be undesirable as acceptability suffers. To standardize the best formulation as determined by Phases 1 and 2 (ISP as emulsifier and the pre-emulsion at 15% incorporation), a bench scale production was also conducted. Two replicates of 5kg each were produced and were also subjected to the same tests in the previous phases. Flavor and acceptability of the sausages were found to be consistent.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Meat -- Preservation; Sausages